Evidence for mitochondrial genetic control of autosomal gene expression. (18th October 2016) - Kassam, Irfahan; Qi, Tuan; Lloyd-Jones, Luke; Holloway, Alexander; Jan Bonder, Marc; Henders, Anjali K.; Martin, Nicholas G.; Powell, Joseph E.; Franke, Lude; Montgomery, Grant W.; Visscher, Peter M.; McRae, Allan F.
Abstract: The mitochondrial and nuclear genomes coordinate and co-evolve in eukaryotes in order to adapt to environmental changes. Variation in the mitochondrial genome is capable of affecting expression of genes on the nuclear genome. Sex-specific mitochondrial genetic control of gene expression has been demonstrated in Drosophila melanogaster, where males were found to drive most of the total variation in gene expression. This has potential implications for male-related health and disease resulting from variation in mtDNA solely inherited from the mother. We used a family-based study comprised of 47, 323 gene expression probes and 78 mitochondrial SNPs (mtSNPs) from n  = 846 individuals to examine the extent of mitochondrial genetic control of gene expression in humans. This identified 15 significant probe-mtSNP associations ( P < 10 − 8 ) corresponding to 5 unique genes on the mitochondrial and nuclear genomes, with three of these genes corresponding to mitochondrial genetic control of gene expression in the nuclear genome. The associated mtSNPs for three genes (one cis and two trans associations) were replicated ( P <  0.05) in an independent dataset of n  = 452 unrelated individuals. There was no evidence for sexual dimorphic gene expression in any of these five probes. Sex-specific effects were examined by applying our analysis to males and females separately and testing for differences in effect size. The MEST gene was identified as having the most significantly different effect sizes across the sexes ( P ≈ 10 − 7 ). MEST was similarly expressed in males and females with the G allele; however, males with the C allele are highly expressed for MEST, while females show no expression of the gene. This study provides evidence for the mitochondrial genetic control of expression of several genes in humans, with little evidence found for sex-specific effects.